Językowe i pozajęzykowe mechanizmy kształtowania pamięci zbiorowej w popularnonaukowym programie „Historia bez Cenzury” - Wójcik, Agnieszka (Stylistyka, 2020)
The subject of interest of the paper is Historia bez Cenzury (“History Uncensored”), a popular series of historical educational videos. The series can be recognised as an effective tool for the shaping of the collective memory of the young generation thanks to the intriguing content of the programme, as well as its linguistic and visual attractiveness. The analysis has revealed two basic communication strategies that serve this purpose; the first is somatisation, that is, concentration on the corporeality of historical figures, and the other is the modernisation of form – which has been used in the series on the linguistic (lexis and phraseology) and the cultural (allusions to the modern world) levels. The aim of the paper is the presentation of linguistic and (to a lesser degree) non-linguistic exponents of these mechanisms.